On the persistence of the ephemeral: presentation of the Special Issue “Black and Peripheral Poetics in the Latin American context” – 2 - Monteiro, Altemar Gomes; Silva, Anderson Feliciano da; Martins, Soraya (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
Presentation of the Special Issue “Black and Peripheral Poetics in the Latin American context” – 2